Analisis Penghalang-Penghalang Komunikasi Mahasiswa-Pembimbing Pada Masa Pandemi Covid-19 - Aulia Rahmawati (LPPM Stikosa - AWS, 2020)
The need for better relationship between students-supervisor intensifies especially during the final years. A good communication and better social interaction between students and supervisors will assure the research process and thesis writing executed effectively. However, the pandemic of Covid-19 has conjured several barriers. This paper explored the way in which barriers emerged during the mentoring process of final year students and their supervisors amidst the condition of Covid-19 pandemic. It doing so by generating interviews as well as focus-group-discussions with 24 final-year students. This paper concludes that at least five communication barriers are identified during the research process in April-May 2020. They are semantic, individual, interpersonal, physical-media and technological barriers. The need for viable solution is suggested, especially in the hands of the University boards.